The Effects of Thyme on IL-6 Level and the Bacterial Count in the Brain and Spleen of Mice Infected by Methicillin-Resistant Staphylococcus aureus (MRSA) - Prasetyowati, Lisayani; Sofro, Muchlis Achsan Adji; Farida, Helmia; Yulieta, Galuh (Fakultas Kedokteran Universitas Brawijaya, 2020)
The extensive and irrational use of antibiotics causes resistance problems such as Methicillin-Resistant Staphylococcus aureus (MRSA). Widespread bacterial resistance to the existing antibiotics promotes the importance of discovering antibacterial sources or modulating the immune response from natural ingredients. This study aimed to reveal the potential of thyme (Thymus vulgaris) extract in reducing IL-6 level and MRSA bacterial count in the brain and spleen of Balb c mice infected by MRSA. The design of this study was a randomized post-test control group. This study used 30 male BALB/c mice infected by MRSA and randomly divided into six groups. Measurement of IL-6 level was carried out using ELISA. The MRSA count was done by assessing the number of CFU per gram of tissue. There were no bacteria in the spleen tissue of all the groups. The IL-6 level in BALB/c mice infected with MRSA and treated with Thymus vulgaris was higher compared to those without Thymus vulgaris (p<0,005). The greatest decrease in microbial count in the brain was among groups that were given the combination of thyme and amoxicillin. Thymus vulgaris extract can elevate the antibacterial effectiveness of amoxicillin.Â